HUBUNGAN DUKUNGAN KELUARGA DENGAN PENERIMAAN DIRI PADA RESIDEN REHABILITASI DI LRPPN BHAYANGKARA INDONESIA MEDAN - Ningsih, Siska Dwi; Mora, Indo; Ramadhani, Sri; Tarihoran, Mia Solistika (JURNAL PSYCHOMUTIARA, 2022)
After receiving the status of being a resident and undergoing the rehabilitation process, the negative stigma they received from the community had an impact on their self-assessment. During the pandemic, which limits the scope of socialization and activities as well as government programs for lock down, of course it will limit the number of visits by family members, reducing resident interactions with people from outside rehabilitation. Research This research on "The Relationship between Family Support and Self-Acceptance in Rehabilitation Residents at LRPPN Bhangkara Indonesia Medan" aims to see the relationship between family support and self-acceptance of Rehabilitation residents. The type of research used is quantitative research. It is called quantitative because the research data is in the form of numbers and data analysis uses statistics. The sample taken in this study is the rehabilitation resident of LRPPN Bhayangakara Indonesia, Medan who has undergone the rehabilitation process with a total of 26 people. Based on the results of the study, the value of R = 0.331 indicates the relationship between the two variables is in the low category. The resident's family support is not related to the self-acceptance of the rehabilitation resident of LRPPN Bhyangkara Indonesia Medan